Continuous improvement projects in certified organizations in Iceland: traditional projects or not? - Sigríður Jónsdóttir 1964- (2013)
Globalization, new technology and competition make today’s surroundings ever changing for organizations and customers’ needs and wants change rapidly making customer retention and market shares an uphill battle. Benchmarking organizations place importance on continuous improvement and systematic approach to projects. There is an interest amongst Icelandic organizations to become certified according to the ISO 9001 standard. The standard is based on quality management principles, such as a customer focus, process approach, and continual improvement. In order for actions taken to continually improve the organization there has to be some kind of objectives and performance measures in place. This paper analyses how certified organizations support continuous improvement by studying what kind of process is in place to support continuous improvement; whether continuous improvement is handled like a formal project; who is responsible for carrying out continuous improvement projects; and which project management tools are mainly used for these projects. Umhverfi fyrirtækja er síbreytilegt vegna samkeppni, hnattvæðingar og nýrrar tækni. Þarfir viðskiptavina breytast stöðugt og það gerir fyrirtækjum erfiðara um vik að halda í þá ásamt markaðshlutdeild. Afburðarfyrirtæki leggja mikla áherslu á að tryggja stöðugar umbætur og kerfisbundna nálgun verkefna. Það er áhugi meðal íslenskra fyrirtækja að fá vottun á gæðakerfi samkvæmt ISO 9001 staðlinum sem byggir á nokkrum grunnreglum gæðastjórnkerfa eins og að setja viðskiptavini í forgrunn, ferlisnálgun og stöðugar umbætur. Til að aðgerðir stuðli að stöðugum umbótum fyrirtækis verða markmið og frammistöðumælingar að vera til staðar. Hér verður skoðað hvernig vottuð fyrirtæki stuðla að stöðugum umbótum með því að skoða hvers konar ferli er til staðar til að tryggja þær. Einnig verður kannað hvort stöðugar umbætur séu meðhöndlaðar sem formlegt verkefni, hver sé ábyrgur fyrir umbótaverkefnum og hvort tækjum verkefnastjórnunar sé beitt við þau.